“Special Witness” – Between a Witness and Suspect - Juozapavičius, Audrius (Teisė, 2020)
Article 80 § 1, Article 82 § 3 of the CCP providing that persons who might give testimony about their own possibly criminal activity may be questioned as witnesses with their consent, applying particular rules – so called “special witness” – are being analysed in this article. By revealing factual ground for becoming a “special witness”, its legal status, the author tries to find an answer to a question whether existing system of persons in the law of criminal procedure justifies existence of such a person, and overall whether this legal regulation is justified.
Keywords: special witness; witness; suspect; privilege against self-incrimination